Sustained censorship in BD (2026-03) (Bangladesh) - Voidly (2026)
CRITICAL severity censorship detected in Bangladesh. Confidence: 72%. Data sourced from OONI.
Censorship Incident ID: BD-2026-0210
Keywords: censorship; BD; censorship; critical